(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the complex social structure of Uzbekistan, national-cultural centers play a key role in supporting relationships between the different ethnic groups that live in the country. Located at the crossroads of Central Asian cultures, Uzbekistan has many ethnicities, each with its own traditions and histories. The creation of national-cultural centers is important for promoting cultural exchange and understanding, encouraging cooperation among communities. By hosting cultural events, language classes, and art activities, these centers help break down stereotypes and build social unity. They are not just places to celebrate cultural heritage but also venues for conversation and healing, helping to create a sense of togetherness despite differences. As Uzbekistan works towards a stronger national identity in a global world, the role of these centers becomes more essential, supporting the values of inclusivity and respect needed for peaceful coexistence.